IDENTIFIKASI HAMA TANAMAN CABAI MERAH DAN TEKNIS PENGENDALIANNYA DI KELOMPOK TANI SARI MULYO DESA SUKASARI KECAMATAN AIR PERIUKAN KABUPATEN SELUMA PROVINSI BENGKULU - Taufik Hidayat; Kusmea Dinata; Andi Ishak; Erpan Ramon (Agrica Ekstensia, 2022)
Horticultural commodities are strategic, have high economic value and are widely cultivated by farmers, one of which is red chili. Pests and plant diseases are the main problems faced by farmers, but their control is still not optimal. This problem is also faced by chili farmers in the Sari Mulyo Farmer's Group in Sukasari Village, Air Periukan Subdistrict, Seluma Regency, Bengkulu Province. The area of chili cultivated in this farmer group is about 6 ha every year. The problem faced in this growing season is the attack of pests that have not been able to be controlled by farmers. Therefore, this study aims to identify the types of pests that attack chili plants, the control carried out by farmers, and suggestions for their control. The research was conducted from December 2021 to January 2022 using field observations and interviews with chili farmers. Observations were made by observing pests on chili plants belonging to farmers with an area of 2.5 hectares. Observations were made on the affected plants by observing the types of pests and the symptoms of their attacks. Meanwhile, interviews were conducted to find out the control efforts that have been carried out by farmers. The identification results showed that there were two types of caterpillars that attacked chili plants, namely Spodoptera spp. and Helicoverpa spp. In addition, there is whitefly (Bemisia tabaci) and thrips (Thrips sp.) attacks. The control carried out by farmers has not been in accordance with recommendation on 6 precise control system in controlling chili pests.